ANALYSIS OF THE INFLUENCE OF WORK MOTIVATION ON EMPLOYEE LOYALTY AT QUEST HOTEL SEMARANG - Kenata, Julius Alfian; Andari Tirtadidjaja (Journal of Innovation Research and Knowledge, 2024)
Employee loyalty in carrying out their performance well will create customer satisfaction so that it can reflect the extent to which customer expectations are met by the products or services provided. In carrying out this research there is a goal that the author wants to achieve, namely to find out and analyze the influence of Work Motivation on Employee Loyalty in Quest Semarang Hotels. This research method, namely quantitative, in this research is an approach that is explanatory and explains an object in society. Quantitative research is a research activity where the data processed is in the form of numbers or figures. As the name suggests, the processed data is calculated using mathematical and statistical formulas. Quantitative research functions so that the answer to a problem can be found. As for the research results based on the calculation data above, it is known that the coefficient of determination value is 0.465, where the Work Motivation variable contributes 46.5% to the Work Loyalty variable. 53.5% was influenced by other factors not examined by researchers. Based on the data, it can be concluded that the coefficient of determination value has a value of 0.682, where the data score is close to 1. Therefore, the independent variable in this research, namely Work Motivation (X), is stated to have a large influence on the Work Loyalty variable (Y)